Analisis Profesionalisme Guru Ideal Dalam Menghadapi Tantangan Transformasi Pendidikan Di Era Modern: Studi Di SMAN 12 Luwu - Sri Wahyuni Hasrin; Ramdani Sidik (PT. Citra Media Publishing, 2025)
The transformation of education in the era of modernization requires teachers not only to master the subject matter but also to adapt to technological advancements and curriculum changes. Teacher professionalism is a key factor in creating an effective learning process that meets contemporary demands. This study aims to analyze the level of ideal teacher professionalism in facing educational transformation challenges at SMAN 12 Luwu, located on Jl. Trans Sulawesi, Bunga Eja Village, Kamanre Subdistrict, Luwu Regency. The research used a mixed-method approach, combining data from student questionnaires (36 respondents), teacher observations, and in-depth interviews with five subject teachers and the school principal. The results indicate that teachers demonstrate high professionalism in social and professional aspects, while pedagogical and technological adaptation still require improvement. Teachers showed discipline and the ability to build positive relationships with students, but the integration of digital media in teaching was not yet optimal across all teachers. In conclusion, the teachers at SMAN 12 Luwu have met most of the indicators of ideal professional educators. It is recommended that the school enhance digital teaching training and foster collaboration among teachers to improve adaptive teaching quality in the modern educational landscape.